Cover Image. Issue 4 (7th June 2017) - Unknown
Abstract : The cover image, by Kari S. Kretch and Karen E. Adolph, is based on the Paper The organization of exploratory behaviors in infant locomotor planning, DOI:10.1111/desc.12421 . Photo Credit: NYU Infant Action Lab.